A Systematic Literature Review on Data-Driven Transformational Leadership for Global Competitiveness in Education - Zesti Amelia (Journal of Innovation in Teaching and Instructional Media, 2026)
This study presents a systematic literature review (SLR) examining the integration of strategic analysis and data utilization in transformational leadership. Synthesizing findings from 15 peer-reviewed articles published between 2021 and 2026, the review identifies key themes, gaps, and mechanisms through which data-driven leadership influences teacher performance and educational quality. The results reveal that while transformational leadership is extensively studied, the explicit integration of data-driven decision-making as a core leadership competency remains underexplored. The study concludes that effective educational leadership requires principals to evolve from inspirational figures into data-informed strategists who leverage strategic analysis to target teacher development. The novelty lies in systematically bridging transformational leadership’s behavioral focus with data-driven decision-making’s analytical demands, challenging assumptions that inspiration alone suffices. The proposed conceptual framework offers a testable causal chain linking leader data literacy through strategic analysis to globally competitive education outcomes. Practically, the findings recommend that leadership training programs prioritize data literacy, teacher professional development align with leadership’s strategic analysis, and policymakers establish integrated data systems with accountability frameworks rewarding effective data use. This study contributes to educational leadership literature by providing a theoretical expansion of leadership models, a consolidated research landscape for 2021-2026, and a practical blueprint for embedding data competencies into principal preparation, teacher coaching, and school improvement plans.